2015
DOI: 10.1016/j.exphem.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Potentially therapeutic levels of anti-sickling globin gene expression following lentivirus-mediated gene transfer in sickle cell disease bone marrow CD34+ cells

Abstract: Sickle cell disease (SCD) can be cured by allogeneic hematopoietic stem cell (HSC) transplant. However, this is only possible when a matched donor is available making the development of gene therapy using autologous HSCs a highly desired alternative. We used a culture model of human erythropoiesis to directly compare two insulated, self-inactivating, and erythroid-specific lentiviral vectors, encoding for γ-globin (V5m3-400) or a modified β-globin (βAS3-FB) for production of anti-sickling hemoglobin (Hb) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
1
30
1
Order By: Relevance
“…Globin genes with antisickling properties present such an example. 57 Apart from integration of therapeutic transgenes, GSHs could support addition of exogenous genes that confer new properties to cells. These include drug resistance genes to select gene-modified cells 58 and tumor antigen receptor genes, such as chimeric antigen receptor genes, to mediate antitumor effects.…”
Section: Towards Applications In Human Gene Therapy Diseases and Tranmentioning
confidence: 99%
“…Globin genes with antisickling properties present such an example. 57 Apart from integration of therapeutic transgenes, GSHs could support addition of exogenous genes that confer new properties to cells. These include drug resistance genes to select gene-modified cells 58 and tumor antigen receptor genes, such as chimeric antigen receptor genes, to mediate antitumor effects.…”
Section: Towards Applications In Human Gene Therapy Diseases and Tranmentioning
confidence: 99%
“…We demonstrated that transduction of SCD BM CD34 + cells with this vector reduced deoxygenation-induced sickling of in vitro -derived RBC progeny. 31 To further support use of the V5m3-400 vector in SCD clinical trials, we tested whether SCD mice receiving nonablative irradiation would engraft with γ-globin gene-corrected HSCs to a level sufficient for a therapeutic effect. Transplanted animals averaged 35% HSC chimerism and had HbF levels ≥ 20% in circulating RBCs, which improved anemia and reduced SCD-related pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…[44]. One of the most successful platforms of chimeric antigen receptor T cells for malignancy uses lentiviral vectors to deliver the transgene [51], and other cell products like dendritic cells [52] and CD34+ cells [53] have also been modified with these vectors.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%